If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24x + 27 = 25x + 35 Reorder the terms: 27 + 24x = 25x + 35 Reorder the terms: 27 + 24x = 35 + 25x Solving 27 + 24x = 35 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 27 + 24x + -25x = 35 + 25x + -25x Combine like terms: 24x + -25x = -1x 27 + -1x = 35 + 25x + -25x Combine like terms: 25x + -25x = 0 27 + -1x = 35 + 0 27 + -1x = 35 Add '-27' to each side of the equation. 27 + -27 + -1x = 35 + -27 Combine like terms: 27 + -27 = 0 0 + -1x = 35 + -27 -1x = 35 + -27 Combine like terms: 35 + -27 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| 5-4y+y-1=19 | | 1.8=0.05x-98.40 | | x-7.1=-3.6 | | s+31=24 | | 5x+5=3x-1 | | 4(6x-8)=14 | | 8-2x=4x+2 | | 8x+2=6x | | 8x+2=6x | | 9x-8=8x | | 3.3x+2=x-8 | | -10+x=-1 | | 9k-26=6k-8 | | 6x+21=-39 | | 19-4x=75 | | 8-p=-12-3 | | 1.8=0.5x-98.40 | | -11+x=-3 | | 7=4+x | | 5x+2=6x+13 | | 7x=6x+12 | | y=x^2-3 | | -5x+11=2x+4 | | x-14=-6 | | 2x+8=x+3 | | x+14=27 | | X-7.3=-5.3 | | 12(n+9)=3(36+4n) | | x+(-12)=11 | | -2x+5=2x-7 | | -3y-14=5y+18 | | -4+3x+48= |